Student's Satisfaction on Online Nursing OSCE (ON-OSCE) Assessment Application - Sutrisno, Resti Yulianti; Primanda, Yanuar; Haris, Fahni (IJNP (Indonesian Journal of Nursing Practices), 2020)
Background: Objective Structured Clinical Examination (OSCE) is one of the final assessment components for nursing students. OSCE assessment uses the ON-OSCE (Online Nursing OSCE) application to fulfill the need and overcome the manual OSCE assessment challenges using papers. The manual OSCE assessment with multiple checklists is very detailed and takes a long time in scoring. Besides, the evaluation using papers tends to cause a miscalculation in scoring a total of ratings that can harm the student.Method: This research is a non-experimental study with a descriptive design and cross-sectional approach. The samples were 480 respondents of nursing students. The instrument of assessment of satisfaction was analyzed based on the score accuracy, time to retrieve score, and examiner's attention. Data analysis used descriptive frequency and percentage distributions. Results: Students' satisfaction based on the time to retrieve score revealed that 365 students (76%) were satisfied. Two hundred eighty-five students (59,4 %) were also satisfied with ON-OSCE related to the score accuracy. Regarding the examiners' attention, 273 students (56,9 %) felt the examiners ignored the students' actions. They focused on the laptop to provide an assessment. It could be due to the new ON-OSCE application for the examiners and their unfamiliarity with operating the application.Conclusion: Most students were satisfied with the assessment using the ON-OSCE application to retrieve scores and the score accuracy. However, they were less satisfied with the examiners' attention. The examiners should be more familiar with the ON-OSCE.